Gut bacterial and fungal communities of François’ langur (Trachypithecus francoisi) changed coordinate to different seasons - Liu, Jinyuan; Zou, Qixian; Li, Diyan; Wang, Tao; Han, Jialiang (Frontiers in Microbiology, 2025)
IntroductionFrançois’ langur (Trachypithecus francoisi), an endangered primate endemic to limestone forests in Vietnam and China, relies on gut microbiota to maintain gastrointestinal stability and adapt to dietary shifts. While gut microbial communities are dynamic and sensitive to seasonal and resource variations, their specific responses in François’ langurs remain poorly characterized. This study investigates seasonal variations in the composition and diversity of gut bacterial and fungal communities in this species to enhance understanding of its ecological adaptations.MethodsFresh fecal samples from 22 François’ langurs in Mayanghe National Nature Reserve, China, were collected across four seasons. Bacterial and fungal communities were analyzed using high-throughput sequencing to assess taxonomic composition and α-diversity. Statistical comparisons were conducted to evaluate seasonal differences at phylum and genus levels.ResultsSignificant seasonal shifts occurred in both bacterial and fungal communities. Bacterial α-diversity peaked in warmer seasons, whereas fungal diversity was higher in colder months. At the genus level, Akkermansia (1.3% relative abundance in summer), a mucin-degrading bacterium linked to gut health, dominated warmer seasons. In contrast, the fungal genus Cercophora, associated with plant biomass degradation, was enriched during colder seasons. Seasonal factors strongly influenced microbial structure, with distinct community assemblages observed across all seasons.DiscussionThe inverse diversity patterns of bacterial and fungal communities suggest complementary roles in nutrient extraction under seasonal dietary constraints. Akkermansia’s summer prevalence may reflect enhanced mucin utilization during fruit-rich periods, while Cercophora’s cold-season dominance likely aids cellulose breakdown in leaf-heavy diets. These dynamics highlight the microbiota’s role in optimizing energy harvest from seasonally variable diets. By elucidating microbial seasonal plasticity, this study provides critical insights for developing conservation strategies tailored to the nutritional ecology of François’ langurs.